International Conference Education and Gender 2022: Book of Abstracts (University of Maribor Press, 2022)
The publication presents a collection of abstracts from the international conference Education and Gender. The papers focus on various aspects and intersections between education and gender. Along with the dissemination of the key results of the STELLA project, the publication brings new perspectives on the hidden curriculum, gender stereotyping and other elements in the content of education.